2002
DOI: 10.1002/j.1939-4640.2002.tb02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Chromatin Structure Assay: Its Clinical Use for Detecting Sperm DNA Fragmentation in Male Infertility and Comparisons With Other Techniques

Abstract: The Sperm Chromatin Structure Assay (SCSA) was first described in the December 5, 1980 issue of Science (Evenson et al, 1980a). The data described in that article showed a significant difference between proven fertile and subfertility or infertility in men and bulls and the susceptibility to denaturation of their sperm nuclear DNA. A subsequent study (Evenson et al, 1984) described SCSA data obtained from men with testicular cancer. The data were heterogeneous, and begged the question, what was SCSA measuring?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
777
5
38

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 908 publications
(841 citation statements)
references
References 158 publications
(168 reference statements)
21
777
5
38
Order By: Relevance
“…From large animal and human studies, Evenson and colleagues, who first described SCSA, suggested that threshold of 0-15 %. 16-29 % and >30 % DNA fragmentation index correlate to high, moderate and low fertility potential, respectively [16,18]. The clinical role of sperm DNA damage assessment by SCSA in assisted reproduction has also been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From large animal and human studies, Evenson and colleagues, who first described SCSA, suggested that threshold of 0-15 %. 16-29 % and >30 % DNA fragmentation index correlate to high, moderate and low fertility potential, respectively [16,18]. The clinical role of sperm DNA damage assessment by SCSA in assisted reproduction has also been established.…”
Section: Discussionmentioning
confidence: 99%
“…After complete analysis of the sample, the X-mean (red fluorescence) and Y-mean (green fluorescence) values were recorded manually after selecting gate for sperm cells using FlowJo software (Oregon). Extent of DNA denaturation (damage) was expressed as DFI, which is the ratio of red to total (red plus green) fluorescence, i.e., the level of denatured DNA over the total DNA [18]. The percentage of high DNA stainability cells (HDS) were also recorded in each sample manually from the graph plot.…”
Section: Scsamentioning
confidence: 99%
“…Spermatozoa with increased levels of red fluorescence corresponding to increased levels of sperm DNA fragmentation were distributed outside the main population (green fluorescence; double-stranded DNA) and quantified on the basis of the percentage of spermatozoa with increased red fluorescence (%DFI). %HDS represents spermatozoa with incomplete chromatin condensation [9] and is expressed as the percentage of spermatozoa with high levels of green fluorescence (> 600 channels of fluorescence in this study, Figure 1). …”
Section: Scsa Proceduresmentioning
confidence: 99%
“…754 npg Any failure(s) in this process during spermatogenesis may have a negative effect on male fertility as the highly organized and condensed sperm chromatin is known to have a crucial role in the normal fertilization process and embryo development [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it expresses different fluorescence properties depending on whether the DNA is single-or double-stranded: red in the former case and green in the latter (67,68). In some cases, the SCSA procedure is combined with counting cells and allows simultaneous determination of sperm numbers and concentration.…”
Section: Chromatin Defectsmentioning
confidence: 99%